The Obese Colorectal Surgery Patient: Surgical Site Infection and Outcomes. Issue 8 (August 2018) - Wahl, Tyler S.; Patel, Fenil C.; Goss, Lauren E.; Chu, Daniel I.; Grams, Jayleen; Morris, Melanie S.
Abstract : BACKGROUND: Obese patients undergoing colorectal surgery are at increased risk for adverse outcomes. It remains unclear whether these risks can be further defined with more discriminatory stratifications of obesity. OBJECTIVE: The purpose of this study was to understand the association between BMI and 30-day postoperative outcomes, including surgical site infection, among patients undergoing colorectal surgery. DESIGN: This was a retrospective cohort study. SETTINGS: The 2011–2013 American College of Surgeons National Surgical Quality Improvement Program database was used. PATIENTS: Patients included those undergoing elective colorectal surgery in 2011–2013 who were assessed by the American College of Surgeons National Surgical Quality Improvement Program. MAIN OUTCOME MEASURES: BMI was categorized into World Health Organization categories. Primary outcome was 30-day postoperative surgical site infection. Secondary outcomes included all American College of Surgeons National Surgical Quality Improvement Program–assessed 30-day postoperative complications. RESULTS: Our cohort included 74, 891 patients with 4.4% underweight (BMI <18.5), 29.0% normal weight (BMI 18.5–24.9), 33.0% overweight (BMI 25.0–29.9), 19.8% obesity class I (BMI 30.0–34.9), 8.4% obesity class II (BMI 35.0–39.9), and 5.5% obesity class III (BMI ≥40.0). Compared with normal-weight patients, obese patients experienced incremental odds of surgical site infection from class I to class III (I: OR = 1.5 (95% CI, 1.4–1.6); II: OR = 1.9 (95% CI, 1.7–2.0); III: OR = 2.1 (95% CI, 1.9–2.3)). Obesity class III patients were most likely to experience wound disruption, sepsis, respiratory or renal complication, and urinary tract infection. Mortality was highest among underweight patients (OR = 1.3 (95% CI, 1.0–1.8)) and lowest among overweight (OR = 0.8 (95% CI, 0.6–0.9)) and obesity class I patients (OR = 0.8 (95% CI, 0.6–1.0)). LIMITATIONS: Retrospective analysis of American College of Surgeons National Surgical Quality Improvement Program hospitals may not represent patients outside of the American College of Surgeons National Surgical Quality Improvement Program and cannot assign causation or account for interventions to improve surgical outcomes. CONCLUSIONS: Patients with increasing BMI showed an incremental and independent risk for adverse 30-day postoperative outcomes, especially surgical site infections. Strategies to address obesity preoperatively should be considered to improve surgical outcomes among this population. SeeVideo Abstract athttp://links.lww.com/DCR/A607 .